Triple negative breast cancer in Asia: An insider's view - Wang, C.; Kar, S.; Lai, X.; Cai, W.; Arfuso, Frank; Sethi, G.; Lobie, P.; Goh, B.; Lim, L.; Hartman, M.; Chan, C.; Lee, S.; et al. (W B Saunders co Ltd, 2018)
While tremendous improvement has been made for the treatment of breast cancers, the treatment of triple negative breast cancer (TNBC) still remains a challenge due to its aggressive characteristics and limited treatment options. Most of the studies on TNBC were conducted in Western population and TNBC is reported to be more frequent in the African women. This review encapsulates the studies conducted on TNBC patients in Asian population and elucidates the similarities and differences between these two regions. The current treatment of TNBC includes surgery, radiotherapy and chemotherapy. In addition to the current chemotherapies, which mainly include cytotoxic agents, such as taxanes and anthracyclines, many clinical trials are investigating the potential use of other chemotherapy drugs, targeted therapeutics and combinational therapies to treat TNBC. Moreover, this review also integrates the studies involving novel markers, which will help us to dissect the pathologic process of TNBC and in turn facilitate the development of better treatment strategies to combat TNBC.